Faktor Penyebab Kesejahteraan pada Karyawan: A Systematic Literature Review - M. Rio; Suhadianto; IGAA Noviekayati (PT. Hasba Edukasi Mandiri, 2026)
Employee well-being is a crucial aspect in increasing productivity, job satisfaction, and organizational sustainability. This study aims to identify factors influencing employee well-being based on research published between 2021 and 2026. The study employed a Systematic Literature Review (SLR) method, adhering to the PRISMA 2020 guidelines. The literature search was conducted through the ScienceDirect, Scopus, and Google Scholar databases. Of the 2,486 identified articles, 20 met the inclusion criteria for analysis. The review results indicate that employee well-being is influenced by internal factors, namely psychological capital, self-efficacy, optimism, resilience, mental health, and job satisfaction, as well as external factors, namely employee engagement, organizational support, supportive leadership, work-life balance, organizational culture, work environment, and work flexibility. Conversely, burnout, work stress, high workload, work-family conflict, and job insecurity are factors that decrease employee well-being. These findings suggest that improving employee well-being requires ongoing organizational support and strengthening individual psychological resources.